Jñāneśvarī sarvasva - Keḷakara, Narasĩha Cintāmaṇa, 1872-1947 (SAMP early 20th-century Indian books project ;, 1946)
Study of Jñāneśvarī of Jñānadeva, fl. 1290, classical commentary on Hindu philosophical work Bhagavadgītā